Creative workshop : 80 challenges to sharpen your design skills - Sherwin, David (Cincinnati, Ohio : How Books, 2010)
'Creative Workshop' is based on a seminar crafted to help students & working designers gain broad exposure to a wide range of design disciplines & develop the depth of skills necessary to excel as a working professional.
Keywords: Creative ability -- Problems, exercises, etc; Psychology